Migration forecasting for European part of Russia according to neutral scenario of future using system dynamics - A. V. Stepanov (Путеводитель предпринимателя)
Article presents the forecast of international migration flows for European part of Russia made by using system-dynamic approach of mathematical modeling. Forecast based on condition that dynamics of Russian economy will contain to grow as well as during retrospective period.